Pengaruh Variasi Konsentrasi Nabh4 dan Suhu Operasi Terhadap Nilai Derajat Deasetilasi Kitosan Dari Limbah Cangkang Rajungan - Adi Putra Winarto; Muhammad Fahmi Hakim (Jurnal Syntax Admiration, 2023)
Researchers aim to make chitosan with variations in operating temperature and the addition of NaBH4 at the deacetylation stage. Chitosan is produced through three stages namely demineralization, deproteination and deacetylation. The deproteination process with 3.5% NaOH ratio 1:10 (w/v) was reacted at 80°C for 2 hours, then continued with the demineralization process with HCl 1 N, 1:10 (w/v) ratio reacted at 38°C for 1 hour. For the final stage of making chitosan, a deacetylation process with 60% NaOH is carried out, a ratio of 1:20 (b / v) with the addition of NaBH4 (0.5 and 1) g and variations in operating temperature (100,110,120) °C at the deacetylation stage for 2 hours. In calculating the value of the degree of deacetylation, researchers use the ratio of absorption band A1655 / A3450 to calculate the value of the degree of deacetylation and the baseline method to assist in the calculation, from this calculation, the value of the degree of deacetylation of chitosan is obtained as much. (46.8%, 49.4%, 56.6%, 62.1%, 72.1%, and 74.8%). The best treatment in this study is the deacetylation process temperature of 120 ° C and the addition of NaBH4 concentration as much as 1 g with a deacetylation degree value of 74.8%.